(3QGej hGdcQIs ((3GdbGgQIs (3hKjbIs, 2006)
(3GddYH HGdcQI Lejd(B..(3hdcf gd jecf dfG Cf fdYH aj GdTGQY?JNjd eGPG MOK eY QGej hdYHg HGdcQI aj GdTGQY ?gd MOKJ dg EUGHI?gd hbY Ydj GdCQV?JSeY CUhGJ JSGbW GdRLGL,hZVH GdLOI,hgQH QGej NhakG ef GdYbGHs
(3GdbUI(B--s (3GdfTjO(B--s (3dYHI GdMQha GdCHLOjI(B--s (3dYHI GdCTjGA(B--s (3dYHI GdJdhjfs
(3ef (B4 (3Edj (B9 (3SfhGJs
2
Keywords: (3QGejs -- (3GdcQIs -- (3ehGO SeYjI hHUQjIs; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs